Few-layered graphene reinforced Al-10 wt% Si-2 wt% Cu matrix composites - Berk Şenyurt; Burak Küçükelyas; Mustafa Bellek; Sina Kavak; Gökçe Borand; Deniz Uzunsoy; Duygu Ağaoğulları; Nazlı Akçamlı (Journal of Materials Research and Technology, 2022)
Few-layered graphene (FLG) reinforced Al-10 wt% Si-2 wt% Cu (Al10Si2Cu) matrix composites were fabricated via a powder metallurgical route. FLG powders were produced in an originally designed DC arc reactor via arc discharge method. Al, Si, Cu and FLG powders were subjected to high-energy ball milling at different durations to produce ternary Al alloy with homogeneously dispersed FLG, and bulk composites were fabricated via subsequent uni-axial compaction and pressureless sintering. The effects of varying FLG amounts and milling duration on the properties of the powder and bulk samples were investigated. The characterization of as-blended and mechanically alloyed (MAed) powders and their sintered forms were performed in terms of microstructural, thermal, mechanical, wear and corrosion properties. According to the results, the hardness values of the 4 h MAed Al10Si2Cu-xFLG composites were determined as 102, 154, 191 and 241 HV for x = 0, 1, 2 and 5 wt%, respectively. Despite the greater hardness value of the Al10Si2Cu-5FLG-4h composite, its compressive strength was low due to its brittle structure. The highest compressive strength was shown by the Al10Si2Cu-1FLG as 463 MPa by an approximate increase of 53% compared to that of the Al10Si2Cu matrix. Moreover, the tribology tests showed that FLG addition (up to 2 wt%) improved the wear rate of the Al10Si2Cu matrix. However, a deteriorative effect of FLG on the corrosion resistance of the composites was determined.